KEMAMPUAN BERHITUNG PERMULAAN ANAK TAMAN KANAK-KANAK KELOMPOK B SE-KELURAHAN LENGKONGSARI KOTA TASIKMALAYA - Maesaroh, Maya; Sumardi, Sumardi; Nur, Lutfi (JURNAL PAUD AGAPEDIA, 2019)
ABSTRACTThis study aims to determine the ability to count the beginning of kindergarten children group B village Lengkongsari Tasikmalaya City. This is based on the importance of numeracy skills for early childhood. In addition, the ability to start counting also needs to be developed so that children have the readiness to continue to higher education again that is elementary school. This research is descriptive research using survey method. Population in this research is kindergarten children group B Se-village Lengkongsari Tasikmalaya City. The data retrieval technique is using purposive sampling. The population of this research is Children of Kindergarten of Lengkongsari Urban Village. The results of data analysis of early numeracy skills include the ability to split the numbers 1-10, write 1-10 numbers, the ability of addition and reduction of 1-10 numbers. The ability to spell shows an average of 9.87. In terms of criteria according to Acep Yoni the ability to count is very well developed. Ability to write an average of 9.53 and is in the criteria developed very well. Furthermore, the summation ability of 9.25 and the average abatement capability is 9.08 and is in excellent growing criteria.Â ABSTRAKPenelitian ini bertujuan untuk mengetahui kemampuan berhitung permulaan anak TK kelompok B Se-kelurahan Lengkongsari Kota Tasikmalaya. Hal ini dilatar belakangi oleh pentingnya kemampuan berhitung untuk anak usia dini. Selain itu kemampuan berhitung permulaan juga perlu dikembangkan sehingga anak memiliki kesiapan melanjutkan ke pendidikan yang tinggi lagi yaitu sekolah dasar. Penelitian ini adalah penelitian deskriptif dengan menggunakan metode survey. Populasi dalam penelitian ini adalah anak TK kelompok B Se-kelurahan Lengkongsari Kota Tasikmalaya. Teknik pengambilan data yaitu menggunakan sampling purposive. Hasil analisis data mengenai kemampuan berhitung permulaan yang meliputi kemampuan membilang angka 1-10, menulis angka 1-10, kemampuan penjumlahan dan pengurangan angka 1-10. Kemampuan membilang menunjukan rata-rata sebesar 9,87. Kemampuan membilang sudah berkembang sangat baik (BSB). Kemampuan menulis rata-rata sebesar 9,53 dan berada dalam kriteria berkembang sangat baik. Selanjutnya kemampuan penjumlahan 9,25 dan kemampuan pengurangan rata-rata sebesar 9,08 dan berada dalam kriteria berkembang sangat baik (BSB).